On Globalisation of Regulation - Bob Wessels (Amsterdam Law Forum, 2009)
In this article the opinion that financial regulation should be dealt with on a national, and not on a global scale is criticised. The objections against global regulation are discussed and dismissed. The greater good of a solid global system is inconsistent with maintaining the full force of national social or economic policies. Bob Wessels submits that the best way forward is to look for (a combination of) the best methods of regulation on the basis of geography, the nature of regulation itself (hard law, best practices, guidelines), the function of certain rules in relation to the goals or the expectations they aim to address and the character of these rules. A parallel is drawn with the way in which cross-border insolvencies are regulated, including solutions from practitioners in the global insolvency of Lehman Brothers Group of Companies. Given the essential role courts play the presence of new rules of the international insolvency should be supported by more robust rules for the cross-border judicial coordination of cross-border cases, such as a convention. The body of financial regulation should be guided by international accepted principles and guidelines and international regulation and national implementation should reflect a balance between what is necessary in the light of the past events, while still leaving room for fair national demands and policies. The allocation of clear responsibility and authority to regulating bodies should warrant an efficient and effective answer for what, at the core, is a global problem, related to international financial markets.